Flow-Induced Fatigue Damage of Large Francis Turbines Under Multiple Operating Loads - Pinghu Liu; Xingxing Huang; Tianyu Yang; Zhengwei Wang (Applied Sciences)
The Francis runner is a critical component of the Francis turbine generator unit, playing a central role in converting water energy into rotating mechanical energy that drives the generator in hydropower stations. In-depth analyses of the flow characteristics of the Francis runner under various operating conditions and avoiding fatigue damage of the Francis runner are crucial to the reliability and efficiency of hydropower operation. In this paper, the flow dynamics of a large Francis turbine runner are analyzed under three representative loading conditions—low partial load, high partial load, and full load—and the flow-induced stress of the runner is analyzed under these loading conditions. It was found that the maximum static and dynamics stresses of the runner at three representative loading conditions are located at the chamfered surface where the blade trailing edge connects to the runner crown. The maximum static stresses of the Francis runner are 284 MPa, 352 MPa, and 381 MPa at low partial load, high partial load, and full load, respectively, and they are above the allowable stress limits, as half of the yield stress of the runner material of 550 MPa. The peak-to-peak values of runner dynamic stress at low partial load, high partial load, and full load are 15 MPa, 25 MPa, and 14.6 MPa, respectively. The high stress invoked by the unsteady flow under various loading conditions in this runner was the cause of the fatigue breakage of the runner blades. The results of this investigation have important reference values for mitigating fatigue damage in similar Francis runners and optimizing unit operation.